2021
DOI: 10.3390/polym13030384
|View full text |Cite
|
Sign up to set email alerts
|

Production and Properties of Lignin Nanoparticles from Ethanol Organosolv Liquors—Influence of Origin and Pretreatment Conditions

Abstract: Despite major efforts in recent years, lignin as an abundant biopolymer is still underutilized in material applications. The production of lignin nanoparticles with improved properties through a high specific surface area enables easier applicability and higher value applications. Current precipitation processes often show poor yields, as a portion of the lignin stays in solution. In the present work, lignin was extracted from wheat straw, spruce, and beech using ethanol organosolv pretreatment at temperatures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…This could be explained by the polydispersity of lignin and the different solubility limits of lignins with different molecular structures and weights, which was also found by Buranov et al [32]. Previous studies have also shown the fractionation of lignin by molecular weight in solvent-shifting precipitation, meaning that predominately highmolecular-weight lignin precipitates while low-molecular-weight lignin predominately stays in solution [33,34]. Figure 6 shows the molecular weight distributions of lignin in filtrates from experiments at different initial lignin concentrations.…”
Section: First Experimental Plan: Variation Of Mixing Temperaturementioning
confidence: 71%
“…This could be explained by the polydispersity of lignin and the different solubility limits of lignins with different molecular structures and weights, which was also found by Buranov et al [32]. Previous studies have also shown the fractionation of lignin by molecular weight in solvent-shifting precipitation, meaning that predominately highmolecular-weight lignin precipitates while low-molecular-weight lignin predominately stays in solution [33,34]. Figure 6 shows the molecular weight distributions of lignin in filtrates from experiments at different initial lignin concentrations.…”
Section: First Experimental Plan: Variation Of Mixing Temperaturementioning
confidence: 71%
“…[19,36,[63][64][65] Furthermore, an important parameter in terms of maximizing lignin precipitation and isolation from the organosolv pretreatment liquid product which contains the solubilized lignin and hemicellulose, affecting also the particle size of lignin, is the alcohol to water ratio (usually referred to as the "antisolvent" effect). [66,67] In the present work, the total water to ethanol ratio was set to 4.5, following the tailored washing and precipitation steps (described in the experimental section) that afforded a recovery degree of 60 wt % on initial biomass lignin (with 87 % delignification of the initial biomass). The recovered lignin exhibited very small particle size of less than 1 μm (as discussed below), very low ash content (ca.…”
Section: Lignin Characterizationmentioning
confidence: 99%
“…[5] Another drawback of using lignin is the presence of contaminants, for example, sulfur, that might covalently bind to it, [27] and its dark color can limit its commercial application. [28] 4 | RECENT APPLICATIONS OF LIGNIN-BASED BIOCOMPOSITES 4.1 | Food handling and/or packaging Due to the increased consumers' demands for sustainable products, manufacturers are required to produce naturalbased products without neglecting their physical and mechanical properties, especially for food packaging applications. The biodegradable properties of lignin make it a favorable component to create food packaging because of its syringil and guaiacyl structure.…”
Section: Challenges In Lignin Incorporation Into Polymeric Materialsmentioning
confidence: 99%
“…[ 5 ] Another drawback of using lignin is the presence of contaminants, for example, sulfur, that might covalently bind to it, [ 27 ] and its dark color can limit its commercial application. [ 28 ]…”
Section: Challenges In Lignin Incorporation Into Polymeric Materialsmentioning
confidence: 99%